Peran Kepemimpinan Transformasional dan Motivasi Kerja Terhadap Kinerja Karyawan: Studi Kasus Telkom Plasa Parepare - Nurnaningsih, Nurnaningsih (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
The purpose of this research is to determine how transformational leadership and work motivation partially influence employee performance at Telkom Plaza Parepare, to determine how transformational leadership and work motivation simultaneously influence employee performance at Telkom Plaza Parepare. This research was conducted using quantitative descriptive methods. The data analysis technique used is multiple regression analysis and uses the SPSS for Windows 25 program. The data used in this research uses primary data sourced from the results of questionnaires that have been filled in by the respondents. The results of this research indicate that partial transformational leadership has no effect on employee performance at Telkom Plaza Parepare. With the value, tcount < ttable = -178 < 2.042 and not significant, 0.860 > 0.05. And work motivation partially influences employee performance at Telkom Plaza Parepare. With the value, tcount > ttable 7.027 > 2.042 with a significance of 0.000 > 0.05. And it has a simultaneous effect with a value of fcount > ftable 24.783 > 3.31 and a significant value of 0.000 < 0.05.